Genome sequence of Bradyrhizobium sp. WSM1253; a microsymbiont of Ornithopus compressus from the Greek Island of Sifnos. Issue 1 (December 2015) - Tiwari, Ravi; Howieson, John; Yates, Ron; Tian, Rui; Held, Britanny; Tapia, Roxanne; Han, Cliff; Seshadri, Rekha; Reddy, T.; Huntemann, Marcel; Pati, Amrita; Woyke, Tanja; et al.
Abstract Bradyrhizobium sp. WSM1253 is a novel N2 -fixing bacterium isolated from a root nodule of the herbaceous annual legumeOrnithopus compressus that was growing on the Greek Island of Sifnos. WSM1253 emerged as a strain of interest in an Australian program that was selecting inoculant quality bradyrhizobial strains for inoculation of Mediterranean species of lupins (Lupinus angustifolius, L. princei, L. atlanticus, L. pilosus ). In this report we describe, for the first time, the genome sequence information and annotation of this legume microsymbiont. The 8, 719, 808 bp genome has a G + C content of 63.09 % with 71 contigs arranged into two scaffolds. The assembled genome contains 8, 432 protein-coding genes, 66 RNA genes and a single rRNA operon. This improved-high-quality draft rhizobial genome is one of 20 sequenced through a DOE Joint Genome Institute 2010 Community Sequencing Project.